If it's not what You are looking for type in the equation solver your own equation and let us solve it.
j/9=-6
We move all terms to the left:
j/9-(-6)=0
We add all the numbers together, and all the variables
j/9+6=0
We multiply all the terms by the denominator
j+6*9=0
We add all the numbers together, and all the variables
j+54=0
We move all terms containing j to the left, all other terms to the right
j=-54
| Y=9x1/10 | | 2/3h-5=11 | | c+-65=3 | | 8=2-6u | | q-20=19 | | 15.15=3.19n | | 9x-15=7x-1C | | 27x=2673 | | -72=m+-13 | | 3.64=8(r+2) | | 47=p+21 | | 152y-7=y | | c+75=87 | | 10b-45=43 | | x-588=1346 | | y+55=95 | | y+-44=35 | | b~-38=74 | | –5b–13=–33 | | x2+10x-29=0 | | b—-38=74 | | 6(4+a(=96 | | 5–5(a–6)=50 | | x+123=579 | | 3x+7=5x7-13 | | 3x-47+2x=8=180 | | 18x-5=6x-(x+2)+(x+3)=42 | | n+4.08=19.9 | | 8+m=25 | | 52+2x+22+52=180 | | -14n+17=41 | | -22=-2+4y |